2008
DOI: 10.1353/hpu.0.0036
|View full text |Cite
|
Sign up to set email alerts
|

Access to Appointments Based on Insurance Status in Washington, D.C.

Abstract: In the U.S., emergency departments see millions of patients requiring timely and adequate outpatient follow-up. Using a hypothetical patient presenting with a scripted presentation of hypertension evaluated in the emergency department and requiring close outpatient follow-up, randomly selected providers in the District of Columbia were queried by phone to evaluate their accessibility based on insurance status. Seventy one percent of calls for privately insured hypothetical patients resulted in a successful app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…The high rate of ER visits and hospitalizations among Medicaid-dependent patients might be attributed in part to their relatively poor access to preventive and follow-up care. 2,3 Considered in the context of previous findings, the utilization data from this study, which demonstrate poor access to care among Medicaid patients, highlight the need to improve care across the continuum of preventive, acute, and follow-up care. COPD, chronic obstructive pulmonary disease; ER, emergency room; HF, heart failure.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The high rate of ER visits and hospitalizations among Medicaid-dependent patients might be attributed in part to their relatively poor access to preventive and follow-up care. 2,3 Considered in the context of previous findings, the utilization data from this study, which demonstrate poor access to care among Medicaid patients, highlight the need to improve care across the continuum of preventive, acute, and follow-up care. COPD, chronic obstructive pulmonary disease; ER, emergency room; HF, heart failure.…”
Section: Discussionmentioning
confidence: 55%
“…1 Recent research suggests that these goals are not being met for many publicly insured Americans. [2][3][4][5][6] Medicaid coverage, compared with other insurance types such as commercial or self-pay insurance, has shown an association with poorer access to preventive, acute, and follow-up care. 2,3 The reasons for these discrepancies in care and outcomes based on insurance type are likely multifactorial and could include insufficient funding, sicker patients, and subpar health care providers and organizations.…”
mentioning
confidence: 99%
“…Studies have shown that being uninsured or having government-sponsored insurance decreases one’s ability to obtain ambulatory appointments. 33,34 Thus, one possible explanation for our results is that insurance status and low income are related to an inability to access appropriate follow-up care in an outpatient clinic, which leads to a reliance on the ED for nonurgent issues. Although the host institution does have a trauma clinic, during the study period, patients would have to call and make an appointment to schedule follow-up, typically in 1 to 2 weeks after discharge, depending on whether follow-up was indicated.…”
Section: Discussionmentioning
confidence: 88%
“…One of the reasons for patients with health coverage to use the ED for less-urgent visits may be the need to use after-hour services as well as the inability to get timely appointments at the clinic [24,25]. In this study, we controlled for visits over the weekend when the clinics were closed, but could not control for evening visits during the week.…”
Section: Discussionmentioning
confidence: 99%